2018
DOI: 10.1159/000491784
|View full text |Cite
|
Sign up to set email alerts
|

Labor Induction in Late-Onset Fetal Growth Restriction: Foley Balloon versus Vaginal Dinoprostone

Abstract: Objective: To compare vaginal delivery rate and perinatal outcomes of fetuses with late-onset fetal growth restriction (FGR) undergoing labor induction, depending on the method for cervical ripening (dinoprostone vs. Foley balloon). Material and Methods: We conducted a retrospective cohort study of 148 consecutive singleton gestations diagnosed with stage I late-onset FGR and Bishop score < 7, in which labor induction was indicated at ≥37 + 0 weeks. Before January 2016, cervical ripening was achieved with 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…This was a multicenter, retrospective cohort study involving 5 referral centers in Italy and Spain (Chieti, Madrid, Valencia, Naples, and Modena) between January 2017 and January 2020. A part of the present cohort has been previously reported in another study from one of the participating centers [10]. All consecutive pregnancies fulfilling all the inclusion criteria and none of the exclusion criteria were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…This was a multicenter, retrospective cohort study involving 5 referral centers in Italy and Spain (Chieti, Madrid, Valencia, Naples, and Modena) between January 2017 and January 2020. A part of the present cohort has been previously reported in another study from one of the participating centers [10]. All consecutive pregnancies fulfilling all the inclusion criteria and none of the exclusion criteria were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…A part of the present cohort was reported previously in another study from one of the participating centers. 8 Inclusion criteria were pregnancies complicated by late FGR (gestational age ≥32 weeks of gestation at diagnosis), as defined by the recently proposed Delphi consensus criteria, including 9 :…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The large sample size and the data coming from all referral centers for the surveillance and management of FGR, inclusion of true cases of late FGR as defined by the Delphi consensus criteria 8 and TA B L E 3 Logistic regression predicting composite adverse intrapartum outcome a , uterine tachysystole or cesarean section/operative delivery for non-reassuring fetal status (NRFS) multitude of outcomes explored represent the main strengths of this study. The retrospective, non-randomized design represents the main weakness of the present study, mostly because two interventions are compared.…”
Section: Ta B L E 2 Primary and Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is scarce evidence on which is the best approach for cervical ripening in this scenario. Recently, our group has found that the Foley balloon could be an optimal method due to its lower association with uterine tachysystole when compared to prostaglandins [11]. Nevertheless, we hypothesize that, besides the method used, there may be other factors affecting the outcome of the induction process in this particular group of fetuses.…”
Section: Introductionmentioning
confidence: 87%